Mapping Re-Naturalization Pathways for Urban Ecological Governance: A Spatial Decision-Support Framework Based on Ecosystem Service Valuation - Chengji Shu; Kaiwei Du; Wenbo Cai; Zhengwu Cai; Li Lin (Land)
Traditional urban expansion struggles to balance economic and ecological demands. Intensive development planning based on re-naturalization has become the policymakers’ choice. However, planning-oriented land use patterns and re-naturalization pathways remain difficult to determine. This study developed a spatial decision-support framework integrating ecosystem service valuation (ESV), land-use simulation, and ecological planning for Shanghai. This study assessed the spatiotemporal dynamics of ESV and simulated land use patterns and ESV for 2035 under different scenarios (inertial development, cropland protection, and ecological development). The optimal scenario and corresponding re-naturalization pathways were determined based on the principle of the optimal ESV. The results showed that ESV has declined over the past 20 years (−5.21%/5 years). High-value areas shrank significantly due to ecological space degradation. The planning-oriented ecological development scenario is the optimal scenario, with the highest ESV of CNY 189,240.29 million, which is higher than the status quo, inertia development scenario, and cropland protection scenario by 9.69%, 23.27%, and 9.53%, respectively. Taking the land use patterns under the ecological development scenario as the re-naturalization objective, 12 re-naturalization pathways totaling 686.88 km2 were identified. Cropland to forestland and built-up land to cropland were the largest, accounting for 67.88% and 15.02%, respectively. This study provides valuable insights into ecological planning and re-naturalization in urbanized areas.